Truth in Fiction Reconsidered - Nyberg, Christer (Res Cogitans, 2018)
Possible and narrative worlds are traditionally the most influential tools for explaining our understanding of fiction. One obvious implication of this is considering fiction as a matter of pretence. The theory I offer claims that it is a mistake to take truth as a substantial notion. This view rejects possible worlds and pretence as decisive features in dealing with fiction. Minimalist theory of fiction offers a solution that gives a way to combine a philosophical theory of meaning and views of literary theory. Narrative worlds approach saves its usefulness since its focus is more in the psychological process of reading. Minimalist theory of fiction is based on the minimal theory of truth and the use theory of meaning. The idea of language games as a practice of constructing contextual meanings is also decisive. A sentence is not true because it corresponds to a fact but because it is used in a right way in certain circumstances. The rejection of the possible worlds approach is thus based on the idea that understanding fiction is essentially about recognizing the constant interplay between different texts and contexts. Better understanding makes different interpretations possible.